Design and Implementation of Project Management for Self-Branding Website Using Rapid Application Development - Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research investigates the implementation of the Rapid Application Development (RAD) methodology in the context of website management for personal branding. The background of the study elucidates the increasing importance of personal branding in the digital age and the role of websites as crucial platforms for individuals to showcase their expertise and establish their online presence. Against this backdrop, the research explores how the RAD methodology is applied to streamline the development and management of personal branding websites, emphasizing its iterative, collaborative, and time-efficient approach. The study delves into the principles and phases of RAD, highlighting its suitability for website development projects characterized by evolving requirements and tight timelines. By employing a qualitative research approach, including interviews, surveys, and case studies, the research examines the experiences and perspectives of individuals and organizations utilizing RAD in their website management endeavors for personal branding purposes. The findings reveal several critical insights into implementing RAD in website management for personal branding. Firstly, RAD enables rapid prototyping and iteration, facilitating the timely development and deployment of websites tailored to individual branding needs. Secondly, RAD promotes collaboration and user involvement, ensuring that websites effectively meet user requirements and preferences. Thirdly, RAD's iterative nature allows for flexibility and adaptability, enabling individuals to respond promptly to changes in branding strategies and market dynamics. Overall, the research underscores the significance of RAD as a valuable methodology for developing and managing personal branding websites. By leveraging RAD's iterative, collaborative, and time-efficient approach, individuals create dynamic and engaging online platforms that effectively communicate their expertise, values, and unique brand identity. The findings offer valuable insights and recommendations for practitioners, researchers, and organizations seeking to enhance their branding efforts through effective website management strategies.